Impact of Diminished Expression of circRNA on Multiple Sclerosis Pathomechanisms - Mycko, Marcin P.; Zurawska, Anna E.; Selmaj, Igor; Selmaj, Krzysztof W. (Frontiers in Immunology, 2022)
Circular RNA (circRNA) molecules represent a novel, unique class of endogenous non-coding RNA controlling the expression and function of microRNA (miRNA) and posttranscriptional regulation. Recent studies implicated circRNA in pathomechanism of multiple sclerosis (MS). Hybridization microarray was used to define the circRNA profile in peripheral blood mononuclear cells (PBMC) from 20 untreated patients with relapsing-remitting MS (RRMS: 10 in relapse, 10 in remission) and 10 healthy controls (HC). We analyzed close to 14000 individual circRNA per sample. The discovery set data were validated using quantitative reverse transcription polymerase chain reaction (qRT-PCR) with an independent cohort of 45 RRMS patients (18 in relapse, 27 in remission) and 27 HC. Microarray analysis revealed 246 circRNA differentially downregulated (P < 0.05) in RRMS patients versus HC. We validated two circRNA from three showing lowest levels of differential expression in the RRMS remission versus HC group: hsa_circRNA_101145 and hsa_circRNA_001896. Their expression was significantly decreased during remission in RRMS (P=0.0000332; FC=0.385; P=0.0455; FC=0.591, respectively) and in patients showing lower level of disability (hsa_circRNA_101145 p=0.0695; hsa_circRNA_001896, P=0.0008). Bioinformatic analysis revealed 10 miRNA interacting with these circRNA in a complementary manner and led to the discovery of 3 protein-coding mRNA downregulated in patients with RRMS during remission. These transcripts have previously been implicated in oxidative stress, blood brain barrier permeability, microglia function, extracellular matrix molecules altering microenvironment and inhibiting oligodendrocyte progenitor cells. CircRNA displayed a distinct profile in PBMC from patients with RRMS, and our results may implicate circRNA with low expression in important mechanistic pathways of RRMS.